Effects of High Intensity Interval Training Versus Moderate Intensity Continuous Training on the Reduction of Oxidative Stress in Type 2 Diabetic Adult Patients: Cat - Poblete-Aro, C; Soto-Munoz, M (2015)
INTRODUCTION: Oxidative stress is caused by an imbalance between an excessive production of reactive oxygen species and/or a deficiency in the level of endogenous and exogenous antioxidant defenses. The presence of reactive oxygen species in large concentrations and for long periods is associated with the occurrence of various diseases, including type 2 diabetes mellitus. Exercise represents an effective means for the prevention and treatment of type 2 diabetes mellitus, and is also able to reduce long-term oxidative stress levels. High-intensity interval training has shown to be an efficient and viable option for type 2 diabetes mellitus control. In turn, high-intensity interval training seems to have positive effects on oxidative stress levels by increasing levels of endogenous antioxidants.OBJECTIVE: To assess the validity and applicability of the results regarding the effectiveness of high-intensity interval training compared to moderate intensity continuous training to reduce oxidative stress in patients with type 2 diabetes mellitus and to answer the following question: In adults with type 2 diabetes mellitus, can the method of high-intensity interval training, compared to moderate intensity continuous training reduce oxidative stress levels?METHODS: We performed a critical analysis of the article "Continuous training vs Interval training in glycemic control and macro and microvascular reactivity in patients with type 2 diabetes".RESULTS: No statistically significant differences were observed in concentrations of superoxide dismutase in any of the experimental groups. Only in the interval group a decrease in malondialdehyde regarding control group and baseline (p